2011
DOI: 10.1590/s1806-83242011000600011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different durations of estrogen deficiency on alveolar bone loss in rats

Abstract: The purpose of this study was to morphometrically evaluate the influence of different durations of ovariectomy-induced estrogen deficiency on alveolar bone loss associated with ligature-induced bone loss in rats. Sixty female Wistar rats were randomly assigned to ovariectomy (OVX test group) or sham operation (SHAM control group). The OVX and SHAM groups were each distributed into three subgroups of ten rats each according to the duration of estrogen deficiency (30, 60 and 90 postoperative days). In all groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…However, more recent studies on humans have shown no relation between periodontal disease and alcohol consumption [6][7] . The use of rat models has been applied in the evaluation of periodontal pathogenesis 8 and regarding the influence of risk indicator/factors, such as estrogen deficiency [9][10] , alcohol consumption [11][12][13][14][15][16] , nicotine 17 and simultaneous nicotine and alcohol use 18 on disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies on humans have shown no relation between periodontal disease and alcohol consumption [6][7] . The use of rat models has been applied in the evaluation of periodontal pathogenesis 8 and regarding the influence of risk indicator/factors, such as estrogen deficiency [9][10] , alcohol consumption [11][12][13][14][15][16] , nicotine 17 and simultaneous nicotine and alcohol use 18 on disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that estrogen deficiency may be a risk factor for tooth loss [3,13,24,25], might affect dental implant success or compromise osseous support in totally edentulous subjects, leading to difficulty in wearing dentures. However the contribution of osteoporosis to tooth loss is difficult to demonstrate because teeth can be lost for several reasons other than the loss of bone support [26]. The wide divergence in the literature may be related to several factors such as the sample used, the method of analysis, the region, nutritional status, the time of analysis and the association with other drugs [2,14,18,[26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…However the contribution of osteoporosis to tooth loss is difficult to demonstrate because teeth can be lost for several reasons other than the loss of bone support [26]. The wide divergence in the literature may be related to several factors such as the sample used, the method of analysis, the region, nutritional status, the time of analysis and the association with other drugs [2,14,18,[26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in periodontal conditions are associated with variations in the levels of these substances 1 . In this respect, the use of oral contraceptives plays an important role 2 , as these drugs modify the estrous cycle to prevent pregnancy.…”
Section: Introductionmentioning
confidence: 99%